2008
DOI: 10.1038/gene.2008.62
|View full text |Cite
|
Sign up to set email alerts
|

Positive selection on mammalian MHC-DQ genes revisited from a multispecies perspective

Abstract: Major histocompatibility complex class II DQA and DQB genes have been shown to be under positive selection in certain mammalian species but not in others, fuelling a debate about how their polymorphism has evolved. In this study, we have analysed whether polymorphism in the peptide-binding region (PBR) of DQA (190 sequences, 11 species) and DQB (209 sequences, 7 species) molecules is positively selected by using both approximate (Nei-Gojobori, Li-Wu-Luo and Pamilo-Bianchi-Li) and maximum-likelihood methods. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
17
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
(36 reference statements)
7
17
0
Order By: Relevance
“…The ABS and non-ABS were distinguished based on HLA-DQB1 structure [74]. Phylogenetic trees were reconstructed for Mhc-DQB1 allelic sequences using Mega 5.05, based on the neighbor-joining method with Kimura 2-para model.…”
Section: Methodsmentioning
confidence: 99%
“…The ABS and non-ABS were distinguished based on HLA-DQB1 structure [74]. Phylogenetic trees were reconstructed for Mhc-DQB1 allelic sequences using Mega 5.05, based on the neighbor-joining method with Kimura 2-para model.…”
Section: Methodsmentioning
confidence: 99%
“…We focused on the exon 2 which encodes part of the peptide binding region (PBR) and is the most polymorphic part of this gene. There is evidence that the DQA gene is under positive selection also in other studied mammals, apparently mediated by parasites (Waine et al, 1998;Bryja et al, 2006;Cutrera and Lacey, 2006;Amills et al, 2008;Deter et al, 2008). DQA genotyping and screening is described in detail in Goüy de .…”
Section: Dqa Genotyping and Screeningmentioning
confidence: 98%
“…Although the Z-test might underestimate selection intensity compared with the maximum-likelihood method (Amills et al, 2008), the latter is unsuitable for cases with recombination events (Wilson and McVean, 2006), and the Z-test can give an idea of the intensity of positive and purifying selection. Our results showed that DRB3 and DQA1 were subject to the same selection mechanism in both subspecies (Table 8), with strong positive selection of the DRB3 gene and weak positive (at ABS) and purifying (at non-ABS) selection of DQA1.…”
Section: Differences In Positive and Purifying Selection Between The mentioning
confidence: 99%
“…The classic a and b genes are extremely polymorphic, especially at the antigen-binding sites (ABS) in exon2 (Reche and Reinherz, 2003;Furlong and Yang, 2008). The remarkable polymorphism of MHC genes is believed to be driven by positive selection (Hughes and Yeager, '98;Richman, 2000;Bernatchez and Landry, 2003;Sommer, 2005;Amills et al, 2008) as the host is subject to a wide range of infections by diverse environmental pathogens. Positive selection often involves balancing selection achieved through heterozygote advantage (overdominant selection) and frequency-dependent selection (Takahata and Nei,'90).…”
mentioning
confidence: 99%